2019
DOI: 10.2961/jlmn.2019.01.0002
|View full text |Cite
|
Sign up to set email alerts
|

Early Stage Material Motion and Transient Optical Properties of Metals after Ultrashort Laser Pulse Irradiation

Abstract: Use of lightweight materials to produce automotive body structures is one of the key trends adopted by automotive manufacturers to minimise emission of greenhouse gases, and subsequently, reduction of fuel consumption. Aluminium alloys are one of the promising lightweight materials which are increasingly used for automotive body-in-white structures. Such applications demand both efficient and effective joining/welding methods to produce repeatable, durable and strong joints without significant alteration of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Shorter pulses do not result in a further increase of ablation efficiency. This trend for ultrashort pulsed material ablation of opaque materials is well known [5,6] and can be linked to a change in laser induced stress and pressure waves inside the material [7], influencing photomechanical ablation mechanisms. In [4] it is shown that the pulse duration itself can also have an effect on ablation quality.…”
Section: Resultsmentioning
confidence: 97%
“…Shorter pulses do not result in a further increase of ablation efficiency. This trend for ultrashort pulsed material ablation of opaque materials is well known [5,6] and can be linked to a change in laser induced stress and pressure waves inside the material [7], influencing photomechanical ablation mechanisms. In [4] it is shown that the pulse duration itself can also have an effect on ablation quality.…”
Section: Resultsmentioning
confidence: 97%